Synergistic effect between surfactants and polyacrylates-maleicanhydride copolymers to improve the flow properties of waxy crude oil. Issue 7 (3rd July 2017) - Al-Sabagh, A. M.; Khidr, T. T.; Moustafa, H. Y.; Mishrif, M. R.; Al-Damasy, M. H.
ABSTRACT: Four copolymers were prepared by copolymerization of octadecyl acrylate with maleic anhydride abbreviated as [ODM], the resulted copolymer was reacted with octadecylalcohol [ODMSA], hexadecylamine [ODMCA], benzyl alcohol [ODMBA] and aniline [ODMAn]. Three oil-soluble surfactants were also prepared by esterification of mono, di and tri ethanolamine with oleic acid, abbreviated as [MEAO, DEAO and TEAO]. These compounds were purified and characterized by FTIR, 1 H-NMR and GPC. The prepared copolymers were evaluated individually and mixed with the oil-soluble surfactants and evaluated as flow improvers and pour point depressants for waxy crude oil. It was found that, the polymer with aromatic side chain [ODMBA] exhibited the maximum pour point depression ΔPP = 24°C at concentration 1000 ppm, while the minimum pour point depression was obtained by [ODMCA] which pronounced ΔPP = 15°C at 1000 ppm. Furthermore, the blend [B4] between [ODMBA] and oil-soluble surfactant [TEAO] achieved extra depression of pour point (ΔPP = 30°C). The rheological properties of the treated and untreated crude oil with the polymeric additives were also investigated and it was found that Bingham yield value (τB ) was decreased from 1.63 Pa at 32°C to 0.3 Pa at the same temperature and 500 ppm concentration of [ODMBA]. GRAPHICAL ABSTRACT: